Endomyocardial biopsy: a 21st century diagnostic tool - Gouveia, Rosa; Andrade, Maria; Aguiar, Carlos; Ramos, Sância (Polish Journal of Pathology, 2021)
The question of the utility of Endomyocardial Biopsy (EMB) often and recurrently raises. It is claimed that the image techniques provide identical results without the risks of an invasive procedure. It is a fact that the impressive technico-scientific development of cardiovascular imagological methodologies covers a broad spectrum of diagnosis. It is also a fact that endomyocardial biopsy is not completely risk-free. Yet, when performed by experienced professionals in reference centres, endomyocardial biopsies my disclose a final unexpected nosologic entity, confirm or exclude a proposed diagnosis and, even when not showing specific lesions in the examined samples, EMB may point to a multifocal involvement of the heart that eventually skipped the fragments collected [1, 2, 3].